KADAR PROTEIN, ELASTISITAS , DAN MUTU HEDONIK MIE BASAH DENGAN SUBSTITUSI TEPUNG GANYONG - Lisa Rosalina (Universitas Muhammadiyah Semarang, 2018)
The purpose of this research is to determine of protein content, elasticity, and hedonic quality of Wet Noodle With Substitutes of Canna’s Fluor.The percentage of Canna’s Fluor which used is 0%, 7.5%, 15%, 22.5% dan 30%. The method of this research is various research methods experiments by completely randomized design (RAL) monofaktorial with 5 treatments and 4 replications. Protein content and elasticitys data was analyzed by statistical ANOVA and followed by a further test of LSD whereas the hedonic quality test results were analyzed using Friedman test and Wilcoxon test. Statistical analysis shows an influence (p<0,05) from the amount of canna’s subtitution to protein content and elasticity value of wet noodle, while on hedonic quality in terms of texture and color give a real effect. But in terms of taste and flavor not give an effect, this is shown from value of (p>0,05). The best result of this research is a noodle with 15% Canna’s Subtution with protein content 4,353%, elasticity value 0,048 N/mm2 and mean of hedonic quality 3,28.